Motivasi Mahasiswa Bermain Judi Online - Harya Bagas Wicaksana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This study aims to 1) find out students motivation for playing online gambling; 2) find out the influence of economic factors that students have when playing online gambling; 3) find out students' understanding of the risks of playing online gambling.This research uses qualitative methods, where researchers collect data through interviews and observations. The subjects of this research are students who are 21-23 years old, domiciled in the Special Region of Yogyakarta and play online gambling, totaling 3 people. The data analysis technique used in this research is to transcribe interviews, observations, data reduction, data presentation, then draw a conclusions.The results showed that in 1)playing online gambling there are several similarities, one of which is the motivation in playing online gambling which wants instant money. Another similarity lies in the interest in playing online gambling, where students rely on the surrounding environment such as campus friends, in obtaining link sites or other information related to online gambling.2) An unstable economy, as well as higher self-needs make students play online gambling. In the game, 3)students understand the risks in playing online gambling, such as undergoing punishment, having their data hacked by unknown people, and taking up a lot of time.